2005
DOI: 10.1159/000089060
|View full text |Cite
|
Sign up to set email alerts
|

Abruptio Placentae during Fetal Myelomeningocele Repair

Abstract: Myelomeningocele (MM) is a congenital neural tube defect with serious consequences, including hydrocephaly. An important hope for intrauterine repair is that hydrocephaly may be prevented by reversing the Arnold-Chiari malformation. Three medical centers in the United States are doing trials with this objective. We describe an intrauterine correction of MM in a Brazilian research center of fetal medicine, which resulted in abruptio placentae and fetal death, to illustrate factors that influence fetal-maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…Paek et al [10] and Bouchard et al [11] found that intrauterine MMC repair in fetal sheep averted the development of Chiari malformation. The results obtained in humans confirm these data, although there is a high rate of uterine and fetal complications (eg, oligohydramnios, persistent uterine contractions, premature rupture of membranes, uterine rupture, infection, and fetal death) because of the invasiveness of the surgery [12][13][14][15].…”
mentioning
confidence: 67%
“…Paek et al [10] and Bouchard et al [11] found that intrauterine MMC repair in fetal sheep averted the development of Chiari malformation. The results obtained in humans confirm these data, although there is a high rate of uterine and fetal complications (eg, oligohydramnios, persistent uterine contractions, premature rupture of membranes, uterine rupture, infection, and fetal death) because of the invasiveness of the surgery [12][13][14][15].…”
mentioning
confidence: 67%
“…However, intrauterine surgery has been tested in clinical research as a way of minimizing the deleterious effects of secondary inflammatory injury [1, 26]. Surgical repair of fetal MM may improve neurological functioning in humans [27], although the procedure carries considerable fetal and maternal risks [26, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…One RCT, 11 retrospective cohort studies , one case–control study and six case reports were analyzed. Eighteen studies were published in English and one in the Spanish language.…”
Section: Resultsmentioning
confidence: 99%
“…One RCT 14 , 11 retrospective cohort studies 10,17,19,22 -30 , one case-control study 31 and six case reports 32 In four cases, the endoscopic surgery could not be completed for maternal safety concerns and/or technical difficulties and these surgeries were abandoned 17,25 . In the study by Bruner et al 24 , the analysis of preterm deliveries < 34 weeks was based on the study of Hamdan et al 37 that comprised the same cohort, and described the postnatal outcomes in 100 of the 116 open surgeries.…”
Section: Study Design and Settingmentioning
confidence: 99%